First records of Inocybe melleiconico and I. pararubens for Northern Europe with a new variety from the alpine zone of the Scandinavian mountains - Vauras J.; Larsson E. (Finnish Mycological Society, 2022)
Abstract: Inocybe melleiconica and I. pararubens are reported as new for Northern Europe, from the alpine zone of Scandinavia. I. melleiconica is rather common on rich and more calcareous soils and usually associated with Salix herbacea. I. pararubens seems to be a rather rare species in the alpine zone and only encountered on calcareous soils on wet ground, associated with Salix reticulata and S. herbacea. We describe I. pararubens var. padjelantae to accommodate the alpine collections of I. pararubens. This taxon is also identified from Canada, arctic tundra of Keewatin. I. pararubens var. pararubens is recorded as new for Sweden, where it was found associated with Tilia cordata, on rich calcareous soil on the west coast of the country. I. castaneicolor is identified as a later synonym of I. pararubens. The spores of the alpine collections of both species treated here were found to be clearly broader than the ones given in the original descriptions.